Hibrida Paradigma Fondasionalisme Dan Hermeneutika Menuju Interpretasi Islam Multikultural - Zakiyuddin Baidhawy (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2010)
Abstract: This article tries to explain the foundational entrapment of the logic of modernism, which imprisons interpreters in only one truth. It elucidates a clash between foundationalism and hermeneutics, and offers an alternative to overcome it. This study concludes that foundational textualism (bayani), intuisionism (`irfani), and empericism (burhani) in the history of Islamic thought, claim their own truth. Contemporary chal- lenges presented by post-modernism have shocked social and cultural conventions, systems of belief, statism and foundationalism of thinking, cultures and outlooks, which have been sacralized by Moslem society for long time. In order to look for a way out from this crisis of Islamic thinking, which eventually affects its social praxis, multicultural interpretation should become an alternative for Moslems in promoting Islam as a uni- versal grace for the whole creation. Keywords: Fondasionalisme (foundationalism), hermeneutika (hermeneu- tics), pemikiran Islam (Islamic thought), multikulturalisme (multicul- turalism), interpretasi (interpretation).